A305 ERYTHROMYCIN AND RELATED MACROLIDES FOR GASTROPARESIS. (1st March 2018) - Wijeratne, T; Tan, P; Jowhari, F; Patel, A; Wijeratne, N; Paterson, W G
Abstract: Background: Gastroparesis is a chronic functional gastrointestinal disorder with considerable morbidity, caused by the failure of the stomach to pump its contents in the absence of a mechanical obstruction, and characterized by symptoms related to impaired gastric emptying. Erythromycin is a macrolide antibiotic that is known to have motilin receptor agonist activity. Having an effect similar to that of motilin, erythromycin has been shown to raise the amplitude of antral peristalsis and initiate premature migrating motor complex phase III activity, thereby stimulating gastric emptying. Aims: To evaluate the safety and effectiveness of erythromycin or its derivatives in reducing symptoms and improving mechanical gastric emptying in adults diagnosed with gastroparesis. Methods: Our search included Medline and EMBASE databases. Literature in all languages were searched and translated to English. Clinical trials registers including the Cochrane Library, abstracts from major gastroenterology conferences and dissertations were also screened. Randomized controlled trials, quasi-randomized studies and experimental studies without randomization/allocation concealment were included in which Erythromycin or any other macrolide or its derivative is compared with a placebo in the treatment of gastroparesis. Quality of studies was evaluated using criteria of masking of randomization, masking of intervention, masking of outcome assessment and completeness of follow-up by review authors. Statistical methods included calculation of mean difference, standardized mean difference and odds ratio when appropriate. Ninety-five percent confidence interval was used for estimates of treatment effects. We are in the process of conducting a detailed analysis of the studies. Results: From our preliminary analysis (21 studies, 717 patients), erythromycin and other derivatives do not significantly improve symptoms related to delayed gastric emptying when compared to a placebo within a 7–28 day period. Also, no significant differences were noted between erythromycin derivatives compared to placebo in reported serious adverse events. The general trend of studies showed significant improvement in mechanical emptying over 1–56 days, when erythromycin or its derivatives were compared to either placebo or metoclopramide. Conclusions: From the available literature it is evident that erythromycin and other derivatives improve gastric emptying. This has potential for exploration in specific subgroups of patients where mechanical improvement would offer improved outcomes (i.e. in patients who are mechanically ventilated to avoid aspiration). The trend in evidence for symptom improvement of gastroparesis does not favour erythromycin or other derivatives although a more formal and unified assessment is warranted. Funding Agencies: None